A Pilot Randomised Control Trial Exploring the Feasibility and Acceptability of Delivering a Personalised Modular Psychological Intervention for Anxiety Experienced by Autistic Adults: Personalised Anxiety Treatment-Autism (PAT-A). - Rodgers, Jacqui; Brice, Samuel; Welsh, Patrick; Ingham, Barry; Wilson, Colin; Evans, Gemma; Steele, Katie; Cropper, Emily; Le Couteur, Ann; Freeston, Mark; Parr, Jeremy R. (Journal of Autism & Developmental Disorders, 2024)
Anxiety is commonly experienced by autistic people and impacts on quality of life and social participation. New anxiety interventions are required to effectively meet the needs of autistic people. Personalised Anxiety Treatment-Autism (PAT-A©) is a bespoke, modular approach to treating anxiety in up to 12 sessions. This study explored the feasibility and acceptability of delivering PAT-A© in the UK National Health Service (NHS). A single-blind randomised controlled trial design. Thirty-four autistic adults were recruited via clinical services and randomised to receive either PAT-A© or enhanced treatment as usual (CCSP). Outcome assessments relating to anxiety, quality of life and related constructs were completed at baseline, immediately post intervention; and at 3 and 12 months. Seventy-one percent of the PAT-A© group and 65% of the CCSP met diagnostic threshold for at least three anxiety disorders. Retention was good across both groups, with 82% (N = 14/17) completing the full course of PAT-A© and 71% (N = 12/17) attending both psychoeducational sessions in CCSP. 94% in PAT-A© and 82% in CCSP completed some follow up assessment 3 months post-intervention. Thematic analysis of interview data revealed that many participants valued the personalised approach, developed transferable skills and experienced positive changes to their anxiety. Participants were willing to be recruited and randomised, PAT-A© was feasible to deliver in the NHS and the trial methods and materials were acceptable. Our findings indicate that a fully powered clinical and cost-effectiveness trial of PAT-A© is warranted.